EVALUATION OF THE MAIN FACTORS RELATED TO FAILURES IN THE LONGEVITY OF COMPOSITE RESIN RESTORATIONS OF POSTERIOR TEETH (REMUNOM, 2023)
Resin materials have been gaining prominence in minimally invasive dentistry, as well as proving to be an excellent ally in terms of biocompatibility, adhesion and mechanical resistance. The longevity of composite resin restorations depends on factors involving the dentist, the patient and the technique used. The reasons that interfere with the success of these procedures are discussed in various studies, with posterior teeth being identified as the main elements involved in failures. The aim of this study was therefore to carry out a narrative literature review, with a documentary and observational approach, focusing on the factors that contribute to failures in the longevity of composite resin restorations in posterior teeth. This review searched for articles available for reading on the subject and published between 2005 and 2023. During the search, causes of unsuccessful restorative procedures were evaluated, among which the following were pointed out in common: secondary caries; fracture; parafunctional habits and occlusal disorders; cavity characteristics; operative technique and restorative material; socioeconomic level of the patient. Secondary caries and fractures were reported as the predominant factors in the failure of restorations in posterior teeth.